Penerapan Metode Seven Tools Dalam Pengendalian Kualitas Produk - Diyaa Aaisyah Salmaa Putri Atmaja; Purbawati Purbawati; Mad Yusup (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Borneo Conblock Mandiri faces significant challenges in its monthly production, with an average of more than 50,000 paving units, but the number of defects exceeds 4,500 units. These defects include cracks, breaks, and uneven or jagged surfaces. To overcome this problem, a quality control analysis is proposed using the seven tools method to reduce defects and improve overall product quality. The research results show that in the production of Holand-type paving, the primary defects include 4,965 units (53%) cracks, 2,661 units (29%) broken, and 1,660 units (18%) the surface is not smooth. Human and machine factors were identified as the leading causes of defects in paving. The proposed solution is the addition of a foreman as an additional supervisor, especially in the production process. The new foreman inspects the material more intensively before it is put into the mixer. Hopefully, these steps can reduce the number of defects and improve overall product quality. The expected result of this research is that it can positively impact the productivity and reputation of Borneo Conblock Mandiri. By addressing the root causes of defects and implementing appropriate solutions, companies can improve their production processes and deliver higher-quality products in line with market demands.